Social responsibility and the concept mix in marketing - K. Bhowan; W. A.A. Maguire (South African Journal of Business Management, 1988)
Levitt's famous article, 'Marketing Myopia' (1960), led to widespread acceptance that a marketing orientation is superior to a product orientation and brought the marketing concept to greater prominence. Writers have tended to present the discussion of fundamental concepts in marketing as an historical progression culminating in the marketing concept which is then presented as the ideal orientation, with universal application, for the formulation of an appropriate marketing philosophy. Over the last ten years or so, several writers have questioned this notion; in particular, the importance of an emphasis on product has been stressed. Another matter which has received some attention in the marketing literature is the impact on marketing philosophy of the pressure on firms to behave in a socially responsible manner. The outcome has been the incorporation of this dimension in the marketing concept. In this paper, the authors point out that the selection of marketing concepts by a firm is influenced by the nature of the firm and the conditions prevailing in its environment; the marketing concept is not an automatic choice and it is not appropriate under all circumstances. They argue further that a firm may be better equipped by adopting a marketing philosophy which draws on two or more concepts and that such a 'hybrid' philosophy is more likely to explain the way in which firms shape their marketing philosophy in practice. Under current conditions, all firms are required to consider their stance on social responsibility in formulating strategy. As marketing philosophy is central to strategy formulation, the societal dimension should feature in it; the authors accordingly suggest that this dimension should be incorporated into any of the fundamental concepts comprising a firm's marketing philosophy. This contrasts with suggestions made to date which appear to be limited to the marketing concept.Levitt se beroemde artikel, 'Marketing Myopia' (1960), het daartoe gelei dat algemeen aanvaar is dat 'n bemarkingsorientasie belangriker is as 'n produkorientasie, en het die bemarkingskonsep meer na vore gebring. Skrywers is geneig om die bespreking van fundamentele konsepte in bemarking voor te stel as 'n geskiedkundige progressie wat in die bemarkingskonsep kulmineer, wat dan aangebied word as die ideale orientasie, met universele toepassing, vir die formulering van 'n gepaste bemarkingsformule. Verskeie skrywers het die afgelope tien jaar hierdie begrip bevraagteken; die belangrikheid van produknadruk is veral beklemtoon. 'n Ander saak wat aandag geniet in bemarkingsliteratuur, is die impak van die druk op firmas om op 'n sosiaal verantwoordelike manier op te tree, op bemarkingsfilosofie. Die uiteinde hiervan was die inlywing van die dimensie in die bemarkingskonsep. Die skrywers wys in hierdie referaat daarop dat die keuse van bemarkingskonsepte van 'n firma beinvloed word deur die aard van die firma asook omgewingsomstandighede; die bemarkingskonsep is nie 'n outomatiese keuse nie, en is nie onder alle omstandighede geskik nie. Verder voer hulle aan dat 'n firma beter toegerus kan wees deur 'n bemarkingsfilosofie te aanvaar wat op twee of meer konsepte gebaseer is en dat so 'n 'hibridiese' filosofie des te beter kan verduidelik hoe firmas 'n bemarkingsfilosofie in die praktyk vorm. Daar word van alle firmas verwag om hulle posisie t.o.v. sosiale verantwoordelikheid tydens strategieformulering, te oorweeg. Omdat bemarkingsfilosofie sentraal fungeer by strategieformulering behoort die maatskaplike dimensie 'n rol daarin te speel; die skrywers stel gevolglik voor dat hierdie dimensie ingesluit word in enige van die fundamentele konsepte wat 'n firma se bemarkingsfilosofie uitmaak. Dit kontrasteer met voorstelle tot op hede wat blykbaar tot die bemarkingskonsep beperk was.
Keywords: 650